2012
DOI: 10.1186/1742-2094-9-37
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of HmC1q with leech microglial cells: involvement of C1qBP-related molecule in the induction of cell chemotaxis

Abstract: BackgroundIn invertebrates, the medicinal leech is considered to be an interesting and appropriate model to study neuroimmune mechanisms. Indeed, this non-vertebrate animal can restore normal function of its central nervous system (CNS) after injury. Microglia accumulation at the damage site has been shown to be required for axon sprouting and for efficient regeneration. We characterized HmC1q as a novel chemotactic factor for leech microglial cell recruitment. In mammals, a C1q-binding protein (C1qBP alias gC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 48 publications
2
23
0
Order By: Relevance
“…In the leech CNS, Hm C1q contributes to the microglial recruitment by interacting with a recently characterized receptor, named Hm C1qBP, which is homologous to mammalian gC1qR [26]. The present report shows the involvement of a second receptor in the C1q-dependent microglial activation.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…In the leech CNS, Hm C1q contributes to the microglial recruitment by interacting with a recently characterized receptor, named Hm C1qBP, which is homologous to mammalian gC1qR [26]. The present report shows the involvement of a second receptor in the C1q-dependent microglial activation.…”
Section: Introductionsupporting
confidence: 53%
“…We also reported that Hm C1q exerts its chemotactic functions on leech microglia by recognizing at least one receptor homologous to human gC1qR (C1qBP) [26]. …”
Section: Discussionmentioning
confidence: 99%
“…The production of the recombinant form of Hm C1q permitted specifying its importance in the microglia migration into the connectives [74]. As discussed above, ex vivo experiments can be performed on the isolated segment of nerve cord maintained in tissue culture.…”
Section: The Leech Microgliamentioning
confidence: 99%
“…Then, the existence of a receptor for Hm C1q (called Hm gC1qR or Hm C1qBP) in the leech CNS has been demonstrated following its molecular characterization from leech databases [74]. The involvement of Hm C1qBP in Hm C1q-dependent chemotaxis has been definitely ascertained showing the inhibition of Hm C1q effect on in vitro leech microglia migration by using anti-C1qBP antibodies.…”
Section: The Leech Microgliamentioning
confidence: 99%
“…C1QBP is commonly localized in the mitochondrial matrix, although it exhibits differential localization among cell lines under various physiological conditions (1). Moreover, it serves important roles in various biological processes, including inflammation, infection, cell signaling and chemotaxis (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%